Structure and function of membrane proteins important in synaptic signalling - Li, A (2024)
Membrane proteins are integral to synaptic signalling. This DPhil project explores the structures and functions of the muscle-type nicotinic acetylcholine receptor (AChR), a ligand-gated ion channel, and the SLC1 family of glutamate transporters.